Benefit of cardiopoietic mesenchymal stem cell therapy on left ventricular remodelling: results from the Congestive Heart Failure Cardiopoietic Regenerative Therapy (CHART‐1) study. (31st May 2017) - Teerlink, John R.; Metra, Marco; Filippatos, Gerasimos S.; Davison, Beth A.; Bartunek, Jozef; Terzic, Andre; Gersh, Bernard J.; Povsic, Thomas J.; Henry, Timothy D.; Alexandre, Bertrand; Homsy, Christian; Edwards, Christopher; et al.
Abstract: Aims: Left ventricular (LV) reverse remodelling is an important marker of improved outcomes in patients with advanced heart failure (HF). We examined the impact of the intramyocardial administration of bone‐marrow‐derived, lineage‐directed, autologous cardiopoietic mesenchymal stem cells (C3BS‐CQR‐1) on LV remodelling in patients with advanced HF enrolled in the CHART‐1 study. Methods and results: Patients ( n =351) with symptomatic advanced HF secondary to ischaemic heart disease, and reduced LV ejection fraction (LVEF <35%) were randomized to receive C3BS‐CQR‐1 or a sham procedure. In a post hoc analysis we examined the effect of C3BS‐CQR‐1 on LV reverse remodelling within 1 year of the procedure and the influence of C3BS‐CQR‐1 dosing in the 271 patients treated as randomized. Delivery of C3BS‐CQR‐1 was associated with a progressive decrease in both LV end‐diastolic volume (LVEDV) and end‐systolic volume (LVESV) within 52 weeks after treatment. At 1 year, the LVEDV and LVESV of treated patients decreased by 17.0 mL and 12.8 mL greater than controls ( P =0.006 and P =0.017, respectively). The effect on LVEDV was maintained after multivariable adjustment for baseline age, systolic blood pressure, LVEDV, LVEF and history of myocardial infarction. The largest reverse remodelling was evident in the patients receiving a moderate number of injections (<20). Conclusion: In CHART‐1, intramyocardial administration of cardiopoietic stem cells led to reverse remodelling as evidenced by significant progressive decreases in LVEDV and LVESV through the 52 weeks of follow‐up. Further studies are needed to explore the dose response with regard to cell number and injected volume, and reverse remodelling.